Embedding Innovation and Technology in HR Practices and its Effects on Organizational Performance (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study shows how using innovation and technology in Human Resource (HR) practices can improve an organization’s performance. It aims to understand how these tools help make HR processes more efficient and boost overall success.Methods: The research used a survey to gather information from 404 employees in sectors such as banking, tourism, public health, education, and civil service. The survey was shared online, and the answers were analyzed using IBM SPSS and Amos software. Different statistical methods were used to find connections between innovation, technology, and organizational performance.Results: The findings show that using innovation and technology in HR practices leads to better organizational performance. When innovation and technology are used together, they have the biggest positive impact, making processes more efficient and improving employee satisfaction.Conclusion: Integrating innovation and technology into HR practices helps organizations improve their operations and keep employees happy. Organizations that use these tools are better able to stay competitive and grow. HR managers should focus on using these strategies to improve their processes and ensure long-term success.